Exploring laryngeal effects of dorsolateral periaqueductal grey stimulation in anesthetized rats: implications for c-Fos and FOXP2 expression in the nucleus ambiguus subdivisions. - Carrillo-Franco, Laura; González-García, Marta; Morales-Luque, Carmen; Díaz-Casares, Amelia; Ponce-Velasco, Marina; Gago-Calderón, Belén; Dawid-Milner, Marc Stefan; López-González, Manuel Víctor (My University, 2024)
Stimulation of the Periaqueductal Gray matter (PAG) and nucleus retroambiguus (nRA) evokes vocalization (1). The nRA serves as a key target for converting passive into active expiration by modulating the activity of laryngeal motoneurons located in the nucleus ambiguus (nA) (2). Previously, we have demonstrated the involvement of rostral and ventral pontine structures in altering laryngeal caliber (3). Furthermore, a heightened expression of the FOXP2 protein (a transcription factor closely linked to vocalization) has been observed in both mesencephalic (PAG) and pontine regions implicated in cardiorespiratory control (4). To investigate the potential interactions between the dlPAG and laryngeal motor neurons of the nA assessing the double staining patterns of c-Fos/FoxP2 protein immunoreactivity (c-Fos-ir/Fox-P2-ir) and Tyrosine Hydroxylase (TH) across the rostro-caudal extent of the nA. Experimental studies were carried out with non-inbred male rats (n=10), SPF, Sprague-Dawley (250-300 g). Animals were anesthetized with sodium pentobarbitone (60 mg/kg i.p., initial dose, supplemented 2mg/ kg, i.v.). The pattern of immunohistochemical and immunofluorescence staining for c-Fos and FOXP2 protein immunoreactivity (c-Fos-ir/FOXP2-ir) were examinated throughout the rostrocaudal extent of the nA region during electrical stimulation of the dlPAG. Guanethidine was administered to suppress sympathetically mediated cardiovascular responses. Stimulation of the dlPAG induced a specific increase in c-Fos-ir, with ipsilateral predominance in the somatas of both the loose (p<0.05) and compact formation (p<0.01) within the nA. Furthermore, we could confirm the bilateral expression of FoxP2 across all domains within the nA. Our study contributes with new data on the role of the mesencephalic neuronal circuits in the control mechanisms of subglottic pressure and laryngeal activity.
Keywords: Neuronas motoras; Laringe - Inervación; dlPAG; c-Fos; FoxP2; Nucleus ambiguus; Laryngeal motoneurons